Pengawasan Dinas Tenaga Kerja Indonesia terhadap Perusahaan Jasa Tenaga Kerja pada Kota Medan - Fatya Nabila (LPPM IAI Nasional Laa Roiba Bogor, 2023)
The Medan City Manpower Office stipulates a minimum wage which is the lowest monthly wage received by workers/labourers as a safety net for workers from the arbitrariness of employers in giving wages to workers. The non-implementation of the provision of the minimum wage by employers has an impact on the occurrence of industrial relations disputes between employers and workers/laborers. In this study, the formulation of the problem is how is the supervision of the Medan City Manpower Service regarding the implementation of the 2017 minimum wage in Medan City? What obstacles occurred in supervising the implementation of the 2017 minimum wage in the city of Medan? Labor inspection is carried out to monitor compliance with labor laws and regulations carried out by labor inspectors from the Medan city manpower and transmigration office which is also based on chapter XIV of Law no. 13 of 2003 concerning Manpower. the research method used is qualitative and naturalistic. Based on the research results, it was found that many workers in the city of Medan had not received normative rights in accordance with Law no. 13 of 2003 concerning Manpower, including non-payment of wages in accordance with the minimum wage, termination of employment (PHK) and payment of overtime wages that are not in accordance with the provisions by employers. These workers feel that their rights are not protected by the government, especially the Department of Manpower and Transmigration as the employment agency. Keywords: Supervision, employment, law no. 13 of 2003